2019
DOI: 10.1111/anu.13009
|View full text |Cite
|
Sign up to set email alerts
|

Substitution effect of Undaria pinnatifida with citrus ( Citrus unshiu , Marcovitch) peel by‐product in feed on the growth, body composition and air exposure stressor of juvenile abalone ( Haliotis discus , Reeve 1846)

Abstract: Substitution effect of Undaria pinnatifida with citrus peel by‐product (CPB) on growth, body composition and air exposure stressor of abalone was determined. A total of 1,080 abalone were distributed into 18 net cages. Five formulated diets were prepared in triplicate. The CPB0 diet contained 200 g/kg U. pinnatifida. The 250, 500, 750 and 1,000 g/kg U. pinnatifida were substituted with the equal amount of CPB, referred to as the CPB250, CPB500, CPB750 and CPB1000 diets, respectively. Finally, dry U. pinnatifid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
(124 reference statements)
1
2
0
Order By: Relevance
“…This could be one of reasons why abalone fed all formulated diets outperformed abalone fed S. japonica in the present investigation. This result is consistent with previous studies by Yun et al (2020) and demonstrating that abalone (H. discus) fed nutrition-balanced formulated diets grew better than abalone fed single MA because of the high water stability in the former.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This could be one of reasons why abalone fed all formulated diets outperformed abalone fed S. japonica in the present investigation. This result is consistent with previous studies by Yun et al (2020) and demonstrating that abalone (H. discus) fed nutrition-balanced formulated diets grew better than abalone fed single MA because of the high water stability in the former.…”
Section: Discussionsupporting
confidence: 93%
“…Hu et al (2012) also demonstrated that administration of leaves as well as stems of broccoli improved superoxide peroxidase and catalase activities, and total antioxidant capability of breast muscle in broiler chickens. Similarly, Jeong et al (2020) and Yun et al (2020) also claimed that dietary substitution of MA with some agricultural by-products containing several bioactive compounds increased the survival of abalone (H. discus) after being exposed to air for a period of time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation